2013
DOI: 10.1063/1.4812236
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for ion injection and transport in conducting polymers

Abstract: We present a simple analytical model that describes ion transport in a planar junction between an electrolyte and a conducting polymer film. When ions are injected in the film, holes recede, leading to partial dedoping of the film. This is modeled by two resistors in series, an ionic one for the dedoped part and an electronic one for the still-doped part. We show that analytical predictions can be made for the temporal evolution of the drift length of ions and the current, variables that could be assessed expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
43
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 23 publications
6
43
2
Order By: Relevance
“…4A indicates that the cationic drift is affected by the In detail, the position of the shoulders found in both 490 cases are related to the time taken by the doping front to 491 reach the metallic electrode, as reported in the case of 492moving-front measurements carried out on P3HT[38]. (shoulders at tens of seconds) is about 10 À4 cm 2 V À1 s À1 .499 A similar result has been found in literature[39].For d = d 1 , the arising of the broad peak can be related to 501 the formation of liquid pathways in the polymer bulk and, 502 specifically, to the reaching of the grounded electrode by 503 the adsorbed liquid. The diffusivity of water in PEDOT:PSS 504 has been widely studied, showing that the dynamics of 505 water diffusion occurs on larger timescales than those 506 involved in charge carriers drift [40].…”
supporting
confidence: 77%
See 1 more Smart Citation
“…4A indicates that the cationic drift is affected by the In detail, the position of the shoulders found in both 490 cases are related to the time taken by the doping front to 491 reach the metallic electrode, as reported in the case of 492moving-front measurements carried out on P3HT[38]. (shoulders at tens of seconds) is about 10 À4 cm 2 V À1 s À1 .499 A similar result has been found in literature[39].For d = d 1 , the arising of the broad peak can be related to 501 the formation of liquid pathways in the polymer bulk and, 502 specifically, to the reaching of the grounded electrode by 503 the adsorbed liquid. The diffusivity of water in PEDOT:PSS 504 has been widely studied, showing that the dynamics of 505 water diffusion occurs on larger timescales than those 506 involved in charge carriers drift [40].…”
supporting
confidence: 77%
“…In particular, the effect of film hydration on device performance is 36 evaluated by studying its electrical response as a function of the spatial position between 37 the electrolyte and the channel electrodes. This is done by depositing a PEDOT:PSS film on 38 a super-hydrophobic surface aimed at controlling the electrolyte confinement next to the 39 electrodes. The device response shows that the confinement of ionic liquids near to the 40 drain electrode results in a worsening of the current modulation.…”
mentioning
confidence: 99%
“…When we use the device (without cells) as an example, we arrive at a hole transit time of 9.2 ls, which is on par with measurement of constant gate current transients on the same device yielding s e ¼ 11.1 ls (not shown). 26,27 This approach thus presents a more rapid method to determine OECT-based materials and device properties. Figure 2, right, shows that the measured impedance (from I G ) matches the shape of the I D transformed impedance (from I D ).…”
mentioning
confidence: 99%
“…The moving front experiment has shown that drift of ions is important for understanding electrochemical doping/dedoping in conjugated polymer films, [25][26][27][28] a fact that is often neglected in the interpretation of electrochemical impedance data. The latter describe ion transport in the film primarily as a result of diffusion, driven by the accumulation of ions at the electrolyte/polymer interface.…”
mentioning
confidence: 99%
“…In hydrated films that support high ion mobilities, however, ions enter the film with ease, leading to negligible potential drop at the electrolyte/polymer interface. 25 As a result, drift plays a significant role in bringing ions in the film and changing the doping level. In this work impedance spectra were determined solely on the basis of drift.…”
mentioning
confidence: 99%